Advances in paper-based sample pretreatment for point-of-care testing. (19th May 2017) - Tang, Rui Hua; Yang, Hui; Choi, Jane Ru; Gong, Yan; Feng, Shang Sheng; Pingguan-Murphy, Belinda; Huang, Qing Sheng; Shi, Jun Ling; Mei, Qi Bing; Xu, Feng
Abstract: In recent years, paper-based point-of-care testing (POCT) has been widely used in medical diagnostics, food safety and environmental monitoring. However, a high-cost, time-consuming and equipment-dependent sample pretreatment technique is generally required for raw sample processing, which are impractical for low-resource and disease-endemic areas. Therefore, there is an escalating demand for a cost-effective, simple and portable pretreatment technique, to be coupled with the commonly used paper-based assay (e.g. lateral flow assay) in POCT. In this review, we focus on the importance of using paper as a platform for sample pretreatment. We firstly discuss the beneficial use of paper for sample pretreatment, including sample collection and storage, separation, extraction, and concentration. We highlight the working principle and fabrication of each sample pretreatment device, the existing challenges and the future perspectives for developing paper-based sample pretreatment technique.